Management of Severe Gunshot Injuries of the Lower Third of the Face: A Case Series and Review - Elia Kassouf, MD; Samer Abou Zeid, MD; Aref Nassar, MD; Marc Aoude, MD; Charbel El Feghaly, MD; Fadi Sleilati, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Major ballistic trauma to the lower face is especially challenging due to its crucial functional and aesthetic roles, involving key soft tissue and bone structures. Proper and timely management of such injuries is crucial, as it can significantly improve both long-term functional recovery and cosmetic outcomes, enhancing the patient’s quality of life. This study reviewed optimal management strategies by presenting a case series of 7 patients. Methods:. We retrospectively reviewed cases involving major gunshot injuries to the lower third of the face, treated at our department over a 10-year period. Patient outcomes were assessed considering both functional and aesthetic results. Results:. Seven patients with bone comminution and varying soft tissue loss were included. Early reconstruction was performed in 5 cases, with 2 receiving free fibula flaps and the rest undergoing osteosynthesis. No primary bone grafting was done. Soft tissue reconstruction required free flaps in 2 cases. After a mean follow-up of 5.6 years, 4 patients healed uneventfully. Complications included 1 fibula flap loss, osteitis with fistula, pseudarthrosis, salivary incontinence, and fibrous adhesions. Two patients required multiple bone grafts, and dental rehabilitation was completed in 4 of 5 indicated cases. Cosmetic results were unsatisfactory in 2 total lower lip reconstructions. Conclusions:. We favor conservative debridement and early reconstruction. Extensive bone and tissue loss requires the early use of free flaps. Primary bone grafting was not possible. Secondary operations were needed for optimal functional and cosmetic results.